1996
DOI: 10.1523/jneurosci.16-11-03685.1996
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Type of Programmed Neuronal Death in the Cervical Spinal Cord of the Chick Embryo

Abstract: We examined the massive early cell death that occurs in the ventral horn of the cervical spinal cord of the chick embryo between embryonic days 4 and 5 (E4 and E5). Studies with immunohistochemical, in situ hybridization, and retrograde-tracing methods revealed that many dying cells express Islet proteins and Lim-3 mRNA (motoneuron markers) and send their axons to the somatic region of the embryo before cell death. Together, these data strongly suggest that the dying cells are somatic motoneurons. Cervical mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
63
0

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 79 publications
6
63
0
Order By: Relevance
“…50 Phagocytosis of dying neurons by adjacent neuronal progenitors has been documented in the developing retina and spinal cord. [51][52][53] However, of particular interest are images showing that motor neurons in the developing spinal cord of the cat engulf supernumerary synapses on the motor neuron cell soma. 54 Similarly it has also been shown that injured hypoglossal motor neurons envelop synapses innervating the cell soma.…”
Section: Synaptic Degeneration In Prion Diseasementioning
confidence: 99%
“…50 Phagocytosis of dying neurons by adjacent neuronal progenitors has been documented in the developing retina and spinal cord. [51][52][53] However, of particular interest are images showing that motor neurons in the developing spinal cord of the cat engulf supernumerary synapses on the motor neuron cell soma. 54 Similarly it has also been shown that injured hypoglossal motor neurons envelop synapses innervating the cell soma.…”
Section: Synaptic Degeneration In Prion Diseasementioning
confidence: 99%
“…Early in the process of neurulation, the cells leave the cell cycle and begin expressing Islet-1; they migrate from the ependymal layer to the ventral horn and then subdivide into Islet-1-positive cells in the LMCm and Islet-1-negative ones in the LMCl. After these events, some motor neurons undergo programmed cell death (PCD), which results in the reduction of the initial number of cells [24,25]. For example, in chick lumbar segments, motor neurons are generated from E2 to E4, and then a steep fall occurs in their number from E6 onward when PCD begins.…”
Section: Discussionmentioning
confidence: 99%
“…As a previous study suggested that this PCD is controlled independent of peripheral targets, the fate of individual MNs in the cervical spinal cord may be intrinsically determined. 25 We recently found that dying population appears to be a subgroup of MN that lacks the expression of LIM homeodomain genes Lim-3, and introduction of this transcription factor rescues cervical MN from early PCD (Yaginuma et al, unpublished). Present data show that Bax is inactive in Lim-3-positive MNs (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…32 By contrast, the earlier phase of MN death (E4-E5) occurs independent of target-derived trophic signals. 25 Recent studies demonstrated that this early MN Figure 8 Summary of Bax action in developing neuronal populations in vivo. During early retinal PCD and the period of naturally occurring death of DRG and MNs, the decision to die or survive is regulated by extrinsic factors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation